Hadis dan Politik Sektarian: Analisis Basis Argumentasi tentang Konsep Imamah Menurut Shi‘ah - Andi Rahman (JOURNAL OF QUR'AN AND HADITH STUDIES, 2013)
This article discusses and analyzes the basic reading and argumentation of the Shi‘ite over the issue of political leadership in Islam, compared with that existing in the Sunnite conception. It discusses their argumentation based on their textual and contextual understanding of the Qur’an and Hadith. Sunnites and Shi‘ites have different opinion over whether Islamic leadership are set based on appointment (imamah) or election (khilafah).